Therapeutic Potential of Natural Product-Based Oral Nanomedicines for Stroke Prevention - Mutoh, Tatsushi (J Med Food, 2016)
Cerebral stroke is the leading cause of death and permanent disability in elderly persons. The impaired glucose and oxygen transport to the brain during ischemia causes bioenergetic failure, leading to oxidative stress, inflammation, blood-brain barrier dysfunction, and eventually cell death. However, the development of effective therapies against stroke has been hampered by insufficient oral absorption of pharmaceuticals and subsequent delivery to the brain. Nanotechnology has emerged as a new method of treating cerebral diseases, with the potential to fundamentally change currently available therapeutic approaches using compounds with low bioavailability. This perspective review provides an overview of the therapeutic potential of oral nanomedicines for stroke, focusing on novel natural product-loaded delivery system with potent antioxidant and anti-inflammatory effects.